STRATEGI PROMOSI DC PRODUCTION MELALUI MEDIA SOSIAL DALAM MENAIKKAN POPULARITAS DENNY CAKNAN (Universitas Negeri Surabaya, 2022)
This study aims to determine how the implementation of DC Production's promotion strategy using social media to increase the popularity of Denny Caknan. This research is a qualitative descriptive research with case study method. The paradigm used is the constructivist paradigm where social processes are obtained through actions and interactions created by individuals continuously so as to produce a reality that is owned and experienced individually. Data collection was obtained through observation and in-depth interviews. The results of this study indicate that the promotional strategy used by DC Production is by utilizing social media. Social media plays an important role in promoting the work of Denny Caknan. DC Production uses promotional tools in the form of social media such as Instagram, Youtube and TikTok. Youtube is useful as a showcase for introducing a song, then being promoted or introduced through Instagram and TikTok. Instagram to influence engagement rate through likes and comments. Then the promotional strategy used is personal branding attached to Denny Caknan on his social media. Keywords : Promotion Strategy, DC Production, Social Media, Denny Caknan